The Problem of Water Resources Pollution with Active Pharmaceutical Substances and the Possibility of Its Solving - BEISENOVA, Raikhan; TULEGENOVA, Symbat; TAZITDINOVA, Rumiya; ORKEYEVA, Ainur; BEISENBEKOVA, Zhazira (Journal of Environmental Management and Tourism, 2022)
Environmental pollution by pharmaceutical products has become one of the most significant problems in the modern world. It also touched upon the countries of Central Asia, including Kazakhstan. Pharmaceutical production in the country is growing rapidly, with drugs widely available to the population. This inevitably leads to the fact that a significant part of medicinal compounds gets into the environment and, in particular, into water bodies. It is obvious that pollution of the aquatic environment with various active pharmaceutical compounds harms the aquatic ecosystem, worsens the quality of water, and, subsequently, human health. That is why the need for the inactivation of pharmaceutical products polluting the aquatic environment is so urgent. The objectives of this study were to identify pharmaceutical compounds in the aquatic environment of Kazakhstan and to test the effectiveness of activated carbon as a means for wastewater treatment by adsorption.